Synthesis of antioxidant and antimicrobial bioactive compounds based on the quinoline-hydrazone and benzimidazole structure - Antonius Herry Cahyana; Devin Halim; Laely Amaliyah (Journal of Advanced Pharmaceutical Technology & Research, 2023)
Quinoline and its derivatives are known to have various biological activities such as antibacterial and antioxidant. Therefore, this study aims to synthesize quinoline moiety from isatin and ethyl acetoacetate by Pfitzinger reaction under acidic conditions. The benzimidazole derivative was synthesized from quinoline and o-phenylenediamine by a solvent-less reaction, while the hydrazone derivative was formed by the reaction with hydrazine hydrate and aromatic aldehyde. In addition, 4-hydroxybenzaldehyde was used as an aromatic aldehyde. The four compounds formed were characterized by thin-layer chromatography (TLC), melting point measurement, Fourier-transform infrared, liquid chromatography–mass spectrometry, and ultraviolet-visible spectrophotometry. They were also evaluated for their antioxidant and antimicrobial activities using the 2,2-diphenyl-1-picrylhydrazyl assay and the disc diffusion method, respectively. All compounds showed weak antioxidant activity compared to ascorbic acid; the quinoline-hydrazone derivative showed the best antioxidant activity with IC50 = 843.52 ppm, while the IC50 value for quinoline-benzimidazole was 4784.66 ppm. All synthesized compounds have not been confirmed to be effective against Staphylococcus aureus and Escherichia coli bacteria in a concentration range of 75–1000 ppm. The bioactive compounds based on the quinoline-hydrazone and benzimidazole structures have been successfully synthesized and tested for their activity as antioxidant and antimicrobial agents.